Case for ditch-wide water rights analysis in Colorado - Magnuson, Donald O., author; Smith, Stephen W., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
In Colorado, the pressures on the historic native water rights are tremendous. Senior water rights that have been in place since the 1800's are now frequently changed to accommodate transfers to municipal and industrial use or an environmental use. Senior water rights are also frequently changed as well augmentation is added as a water use. In order to begin a change case in Colorado Water Court, the historic consumptive use (CU) of the water right must be established through an engineering study. Various historic use records, assumptions, period of record, and other elements of the engineering study come under intense scrutiny by objectors in the case and by the Court. Most commonly, ditch companies actually hold the decreed water right and each shareholder in the ditch system owns a proportional amount of that right based on their share holdings. For example, one share out of one hundred shares issued represents one percent ownership of the company and one percent of that water right. In the past, change cases have been initiated, and a new change decree fully adjudicated, in consideration of only a portion of the outstanding shares under the ditch system using what is known as a parcel specific analysis. Issues arise with this in that the amount of shares owned and used to irrigate a certain amount of irrigated ground can vary from one farming operation to another. The pros and cons associated with doing a full ditch-wide analysis of the water right are discussed.
Meeting irrigation demands in a water-challenged environment
Ditch-wide water rights analysis
Presented at Meeting irrigation demands in a water-challenged environment: SCADA and technology: tools to improve production: a USCID water management conference held on September 28 - October 1, 2010 in Fort Collins, Colorado.